2022
DOI: 10.1097/qai.0000000000002899
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HIV on Cognitive Performance in Professional Drivers

Abstract: Background:The intellectually demanding modern workplace is often dependent on good cognitive health, yet there is little understanding of how neurocognitive dysfunction related to HIV presents in employed individuals working in high-risk vocations such as driving. HIV-associated neurocognitive impairment is also associated with poorer long-term cognitive, health, and employment outcomes.Setting:This study, set in Cape Town, South Africa, assessed the effects of HIV on neuropsychological test performance in em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…Recently, a cross-sectional study was conducted in professional drivers. The finding showed that professional drivers with HIV performed significantly poorer neurocognitive functions than those with cardiovascular diseases and healthy controls, especially in processing speed, attention and working memory [ 30 ]. It is worth to examine that the effectiveness of early detection and early treatment of SRBDs in PLWH on preventing the risk of traffic accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a cross-sectional study was conducted in professional drivers. The finding showed that professional drivers with HIV performed significantly poorer neurocognitive functions than those with cardiovascular diseases and healthy controls, especially in processing speed, attention and working memory [ 30 ]. It is worth to examine that the effectiveness of early detection and early treatment of SRBDs in PLWH on preventing the risk of traffic accidents.…”
Section: Discussionmentioning
confidence: 99%
“…[65][66][67][68] This battery of tests has been used extensively in studies of South African PWH. 67,69 The domains, tests, and outcome variables were: (…”
Section: Methodsmentioning
confidence: 99%
“… 62 We clustered tests into cognitive domains according to theoretical knowledge about the construct of each test 63 , 64 and according to standard practice in the field of HIV neuropsychology. 65 68 This battery of tests has been used extensively in studies of South African PWH. 67 , 69 …”
Section: Methodsmentioning
confidence: 99%
“…The battery comprised 12 standardized neuropsychological tests, each of which assessed performance in one of seven cognitive domains commonly affected by HIV (Grant, 2008). This battery of tests has been widely used in South African research (e.g., [ 72 , 73 ]).…”
Section: Methodsmentioning
confidence: 99%